Global health and national borders: the ethics of foreign aid in a time of financial crisis - Johri Mira; Chung Ryoa; Dawson Angus; Schrecker Ted (BMC, 2012)
Abstract Background The governments and citizens of the developed nations are increasingly called upon to contribute financially to health initiatives outside their borders. Although international development assistance for health has grown rapidly over the last two decades, austerity measures related to the 2008 and 2011 global financial crises may impact negatively on aid expenditures. The competition between national priorities and foreign aid commitments raises important ethical questions for donor nations. This paper aims to foster individual reflection and public debate on donor responsibilities for global health. Methods We undertook a critical review of contemporary accounts of justice. We selected theories that: (i) articulate important and widely held moral intuitions; (ii) have had extensive impact on debates about global justice; (iii) represent diverse approaches to moral reasoning; and (iv) present distinct stances on the normative importance of national borders. Due to space limitations we limit the discussion to four frameworks. Results Consequentialist, relational, human rights, and social contract approaches were considered. Responsibilities to provide international assistance were seen as significant by all four theories and place limits on the scope of acceptable national autonomy. Among the range of potential aid foci, interventions for health enjoyed consistent prominence. The four theories concur that there are important ethical responsibilities to support initiatives to improve the health of the worst off worldwide, but offer different rationales for intervention and suggest different implicit limits on responsibilities. Conclusions Despite significant theoretical disagreements, four influential accounts of justice offer important reasons to support many current initiatives to promote global health. Ethical argumentation can complement pragmatic reasons to support global health interventions and provide an important foundation to strengthen collective action.